Network model of decreased context utilization in autism spectrum disorder. - Beversdorf D; Narayanan A; Hillier A; Hughes J (Journal of Autism & Developmental Disorders, 2007)
Individuals with autism spectrum disorders (ASD) demonstrate impaired utilization of context, which allows for superior performance on the 'false memory' task. We report the application of a simplified parallel distributed processing model of context utilization to the false memory task. For individuals without ASD, experiments support a model wherein presentation of one word, e.g., ''apple,'' strongly activates the neighboring nodes of closely related words such as ''fruit,'' ''tree,'' whereas in ASD these neighboring nodes are relatively less activated. We demonstrate this model to be consistent with the superior performance on recognition testing on the false memory test, but not on free recall. This may have an anatomic basis in diminished hippocampal neuronal arborization and the abnormal minicolumnar pathology in ASD.